Sertifikasi Tenaga Kerja Konstruksi: Mengikuti Regulasi Pemerintah Ataukah Meningkatkan Kompetensi Bisnis - Kadek Nita Puri Rahayu (Universitas Pendidikan Nasional, 2019)
ABSTRACTThis study aims to determine whether certification can build business competency or just a mere formality / tick the box. The sampling technique that is done is by conducting interviews with informants and documentation. The informants in the study were determined by purposive sampling method. The informant referred to by the researcher is the first informant or the most suitable key informant is the Project Management Expert who has followed the certification of expertise then the Project Management Expert directs the next informant to the K3 Construction Expert, the K3 Expert Construction then directs the next informant who oversees the course of the project and the Overseer direct the next informant is the Builder who is considered capable of providing information in this study. The results of the study indicate that certification is not a check box / limited to mere formality, but is able to improve the business competencies of the workforce. This can be said by the author because certification is a very important factor to improve the competence and quality of their work, because the skills knowledge gained in the certification program can be applied directly in the field to the maximum, so that the completion of the project is completed on time. The results of the study indicate that certification is not a check box / limited to mere formality, but is able to improve the business competencies of the workforce. This can be said by the author because certification is a very important factor to improve the competence and quality of their work. From the results of interviews conducted by the authors that the implementation of certification has been effective but around 50% of the workforce has not yet received certification. Therefore, the next researcher is expected to be able to explore more specific information about what factors have caused the workforce to not have been certified.